2013 3rd IEEE International Advance Computing Conference (IACC) 2013
DOI: 10.1109/iadcc.2013.6514266
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of AODV, based on mobility model

Abstract: Wireless communication system is gaining to much attention for reliable communication. One of modern communication system is Mobile Ad-Hoc Networks (MANET) and it has several routing protocols for communication. The AODV is the one of efficient protocol for the MANET. In this paper we are proposing a novel technique for modeling for AODV routing protocol. The proposed technique is based on the Markov random walk model. Here we calculate the probability distribution for the several operations for efficient comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Authors both methodologies had a combined effect of lowering the ratio of link failures as well increasing in throughput. Shukla et al [5] had suggested a new MANET methodology by modifying the standard AODV routing protocol. Authors used the concept of Markov random walk algorithm where the available probability strength was used for an effective connection.…”
Section: Pawandeep Kaur Hemant Sethimentioning
confidence: 99%
“…Authors both methodologies had a combined effect of lowering the ratio of link failures as well increasing in throughput. Shukla et al [5] had suggested a new MANET methodology by modifying the standard AODV routing protocol. Authors used the concept of Markov random walk algorithm where the available probability strength was used for an effective connection.…”
Section: Pawandeep Kaur Hemant Sethimentioning
confidence: 99%
“…The difference in these density numbers can determine the behavior of routing schemes. To obtain the best scheme, we simulated AODV [15], DSDV [16] and our proposed routing selection scheme using OMNET++ simulation tools to verify our work. Model verification is important for checking the reliability of the simulation result and for evaluating the scheme.…”
Section: Simulation and Analysismentioning
confidence: 99%
“…These indicators are: performance, protocol overhead, packet dropped, average delay and the variation of the delay or jitter. These indicators are compared with those of the following protocols: CBRP (Chaba et al, 2009), AODV (Shukla et al, 2013) and DSDV (Mahdipour et al, 2009). We entered via a terminal the following directory: ns-allinone then we entered ns2.34/indeputils/cmugen/setdest/setdest in order to create a scenario of 160 nodes with the following command./set-dest-v 160-2-n-m 2 s 1 m 6-t-150-P-1-p 2 x 2000-and 1000.…”
Section: General Parameters For Simulationmentioning
confidence: 99%
“…The advantage of using them, in emergency and rescue scenarios, would be energy savings during communications, since a non-constant network update improves energy saving on mobile devices from people waiting for a communication link to address the evacuation zone. Among the most known reactive protocols are: Dynamic Source Routing (DSR) (Johnson, Hu, & Maltz, 2007) and Ad Hoc Demand Distance Vector (AODV) (Shukla, Jha, Saxena, & Biswash, 2013).…”
Section: Routing Protocols In Ersmentioning
confidence: 99%